Heat transfer phenomenon between electric submersible motor and three-phase flow in oil wells under intensive salt accumulation conditions; Проблемы геологии и освоения недр; Т. 2 - Abdulaev R. K. (Geology, mining and petroleum engineering (English, German), 2012)
Заглавие с титульного листа